Parental involvement and its impact on children's school performance : a study in Sekolah Indonesia Kuala Lumpur - Amri, Khairul (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Many variables associate with children school performance have been investigated. Among other factors, the significance of parental involvement in children's education is unquestionable. An abundance of studies have revealed that parental supports both at school and at home helped to improve their children's performance. Nevertheless there is a scarcity of research involving children in Indonesian schools. Hence there is a need to conduct a study to obtain necessary information on parental-related factors that can give impact on their children's school performance. This study aims to examine the level of parental involvement in their children's education and also the strength of the relationship between their involvements and their children's academic performance, school attendance and school behaviour. Relationship between parents' socioeconomic background and their involvement was also investigated. The samples of the study were 150 parents and 75 children from grades three, four and five respectively in Sekolah Indonesia Kuala Lumpur. This study utilized Family Involvement Questionnaire (FIQ; Perry, Fantuzzo & Munis, 2002) and socio demographic information to collect data from the samples. Descriptive statistics, t-test, simple linear regression and bivariate correlation were employed to analyze the finding of the study. The result of this study revealed that there was a moderate level of parental involvement in their children's education. However this study also found that there was no significant difference between fathers and mothers involvement; there was no significant relationships between the variables of children's education; and also there was no significant relationships between socioeconomic background and parental involvement respectively. This study provide information that parents provided support for their children's education but probably due to their work commitment the involvement is rather moderate. Than it can also be utilized to initiate suitable program to enhance the involvement of parents in maximizing the potential of their children's education.